Studi Komparatif Efektivitas Pembelajaran Kooperatif Model Make A Match Dan Metode Diskusi Di SMP Negeri 1 Kurun Kabupaten Gunung - Liling Lenlioni; Jairi Jairi; Rinto Alexandro (FKIP, Universitas Palangka Raya, 2021)
So far, the learning process tends to be conventional, teachers use the lecture method more and eliminate learning activities. So that students feel bored and not interested in following the learning process, this results in low student learning outcomes. This study aims to (1) describe whether or not there are differences in the make a match model and discussion methods on the learning outcomes of class VIII students at SMPN 1 Kurun, (2) describe the level of effectiveness of learning with the make a match model and discussion method. This study uses a quantitative approach. This research method used an experimental method in the form of a randomized pretest-posttest comparison design using 2 groups of subjects, namely 1 group as the experimental class I (Make A Match) and 1 group as the experimental class II (Discussion). This research was conducted at SMP Negeri 1 Kurun Gunung Mas Regency in class VIIIA and class VIIIB in the 2016/2017 academic year. Sampling using purposive sampling technique. Data collection techniques using tests in the form of pretest and posttest. Analysis of the data before testing the hypothesis using the normality test and homogeneity test, then testing the hypothesis using ttest analysis. The results showed that the learning outcomes of class VIIIA students who used the make a match method were better than class VIII who used the discussion method with an average score of 81.5625 for class VIIIA and 73.1250 for class VIIIB and based on the results of the t-test showed tcount (4.306) > t table (1.959). Thus it can be concluded that learning using the make a match model is more effective in improving student learning outcomes than using the discussion method.